Preparation method of vulcanized polyacrylonitrile fiber composite material for positive electrode of all-solid-state lithium-sulfur battery

Through the preparation method of vulcanized polyacrylonitrile fiber composite material, the problem of poor electronic conductivity and ion transmission efficiency of the positive electrode of all-solid lithium-sulfur battery is solved, and higher capacity release and cycle stability are achieved.

CN119465432AActive Publication Date: 2025-02-18CHINA TOWER CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411559216.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-18
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The positive electrode of all-solid lithium-sulfur battery has poor electronic conductivity and ion transmission efficiency, resulting in insufficient capacity release and poor cycle stability.

Method used

The preparation method of vulcanized polyacrylonitrile fiber composite material is adopted to improve the bound sulfur content and enhance electron and ion transport through the synthesis process of thiol modification, electrospinning, two-step sintering and multiple ball milling.

Benefits of technology

The electronic conductivity and ion transmission efficiency of the positive electrode of all solid lithium-sulfur battery are improved, and capacity release and cycling stability are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465432A_ABST
    Figure CN119465432A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a sulfurized polyacrylonitrile fiber composite material for a positive electrode of an all-solid-state lithium-sulfur battery, and belongs to the technical field of all-solid-state lithium metal batteries, and the preparation method specifically comprises the following steps: mixing a micromolecular organic matter containing a sulfydryl functional group with polyacrylonitrile, sintering to obtain powder A, dissolving the powder A in an organic solvent, heating and stirring to form a precursor solution B, and drying to obtain the sulfurized polyacrylonitrile fiber composite material for the positive electrode of the all-solid-state lithium-sulfur battery. The preparation method comprises the following steps: spinning into a fiber shape through an electrostatic spinning process, drying, crushing, mixing with sulfur powder to obtain a mixture D, sintering to complete the process of vulcanization and removal of crystalline sulfur elementary substance, cooling to room temperature, and ball-milling to obtain fiber particles, thereby obtaining the vulcanized polyacrylonitrile fiber composite material for the positive electrode of the all-solid-state lithium-sulfur battery. Through the synthesis process of sulfydryl modification, electrostatic spinning, two-step sintering and multiple times of ball milling, the binding state sulfur content proportion of the positive electrode is improved, and electron and ion transmission of a three-phase contact interface in the positive electrode is improved, so that the capacity release of the all-solid-state lithium-sulfur battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of all-solid-state lithium metal batteries, and in particular relates to a method for preparing a sulfurized polyacrylonitrile fiber composite material for a positive electrode of an all-solid-state lithium-sulfur battery. Background Art

[0002] As the scale of fossil fuel reserves is decreasing, the uncertainty of future fossil fuel supply and the growing energy demand of mankind have forced many countries to seek other new energy sources to replace fossil fuels. The development of new energy industry is of great significance to the adjustment and transformation and upgrading of my country's energy structure, and chemical power sources, as an important part of the new energy industry chain, have also received more and more attention. As a new type of rechargeable battery, lithium-ion batteries have the advantages of high energy density, long cycle life, environmental protection and low harm, and are widely used in various fields of people's life and travel. With the continuous development of electronic equipment and electric vehicles, the demand for chemical power sources will also increase. Therefore, the development of high-performance lithium-ion batteries with higher energy density and longer cycle life is the only way to develop the new energy industry.

[0003] Lithium-sulfur batteries (Li-S) rely on the phase change chemistry of sulfur Can accommodate more lithium ions. The theoretical specific capacity of lithium-sulfur batteries is as high as 1675mAh g -1 , the theoretical specific energy is up to 2600Wh kg -1, which is 5 to 10 times higher than the most advanced lithium-ion batteries currently available, and has extremely broad application prospects in the field of energy storage equipment (Xu R, Lu J, Amine K. Progress in Mechanistic Understanding and Characterization Techniques of Li-S Batteries [J]. Advanced Energy Materials, 2015, 5 (16)). In traditional liquid lithium-sulfur batteries, due to the high solubility and high mobility of polysulfides in liquid organic electrolytes, the shuttle effect is caused, which ultimately leads to the effective mass loss, low Coulomb efficiency and poor cycle stability of the battery. Therefore, the theoretical specific capacity and theoretical energy density of lithium-sulfur batteries have almost never been achieved (Ren W, Ma W, Zhang S, et al. Recent advances in shuttle effect inhibition for lithium sulfur batteries [J]. Energy Storage Materials, 2019, 23 707-732.). All-solid-state lithium-sulfur batteries use inorganic solid electrolytes, which can fundamentally avoid the shuttle effect caused by polysulfide dissolution and may also inhibit the growth of lithium dendrites to a certain extent (Liu Y, He P, Zhou H. Rechargeable Solid-State Li-Air and Li-S Batteries: Materials, Construction, and Challenges[J]. Advanced Energy Materials, 2018, 8(4)).

[0004] At present, all-solid-state lithium-sulfur batteries generally use sulfur as the positive electrode active material, but due to the extremely poor conductivity of sulfur, its capacity cannot be fully released. Therefore, polyacrylonitrile (PAN, (C3H3N) n ) conductive framework, the sulfur species are bound to the polyacrylonitrile conductive skeleton to obtain a sulfurized polyacrylonitrile (SPAN) positive electrode, which can improve the problem that the capacity cannot be fully released. However, the content of crystalline sulfur in sulfurized polyacrylonitrile is relatively large (>20%), and the conductivity of crystalline sulfur is very poor. Therefore, it is necessary to increase the content of bound sulfur (<20%), thereby improving the electronic conductivity of the positive electrode and ultimately improving the cycle stability of the all-solid-state lithium-sulfur battery. At the same time, in all-solid-state lithium-sulfur batteries, due to the poor solid-solid contact between the active material inside the positive electrode and the electrolyte, the ion transfer efficiency of sulfurized polyacrylonitrile also needs to be improved. Summary of the invention

[0005] In view of the problems of poor electronic conductivity and ion transfer efficiency of existing sulfurized polyacrylonitrile positive electrodes, the present invention provides a method for preparing a sulfurized polyacrylonitrile fiber composite material for an all-solid-state lithium-sulfur battery positive electrode. Through the synthesis process of thiol modification, electrospinning, two-step sintering and multiple ball milling, the proportion of bound sulfur content in the positive electrode is increased, which helps to improve the electron and ion transfer at the three-phase contact interface inside the positive electrode, thereby improving the capacity release of the all-solid-state lithium-sulfur battery.

[0006] In order to achieve the above purpose, the technical method adopted by the present invention is as follows:

[0007] A method for preparing a vulcanized polyacrylonitrile fiber composite material for an all-solid-state lithium-sulfur battery positive electrode comprises the following steps:

[0008] Step 1: mixing a small molecule organic substance containing a thiol functional group with polyacrylonitrile, and sintering the mixture in a rare gas atmosphere or nitrogen to obtain powder A;

[0009] Step 2, dissolving powder A in an organic solvent, heating and stirring to form a precursor solution B;

[0010] Step 3, spinning the precursor solution B into fibers through an electrospinning process, and drying to obtain a fiber film C;

[0011] Step 4, crushing the fiber film C, and mixing it with sulfur powder in a mass ratio of (3-5):1 to obtain a mixture D;

[0012] Step 5, placing the mixture D in a rare gas atmosphere or nitrogen, heating it to 250-450° C., and keeping it warm for 5-8 hours to complete the vulcanization process; then cooling it to 150-200° C., keeping it warm for 2-4 hours to remove the crystalline sulfur element, and cooling it to room temperature to obtain a fiber sintered material E;

[0013] Step 6: ball-mill the fiber sintered material E into fiber particles to obtain a sulfurized polyacrylonitrile fiber composite material for the positive electrode of an all-solid-state lithium-sulfur battery.

[0014] Furthermore, the small molecule organic matter containing a thiol functional group in step 1 is tert-butyl mercaptan, trithiocyanate, cysteine, cysteamine, sodium methyl mercaptan, thioglycolic acid, naphthalene dithiol or mercaptoethylamine hydrochloride, and the mass ratio of the small molecule organic matter containing a thiol functional group to polyacrylonitrile is 1:1 to 5.

[0015] Furthermore, in step 1, the sintering temperature is 150-250° C. and the sintering time is 3-5 hours.

[0016] Furthermore, the organic solvent in step 2 is N,N-dimethylformamide, dimethyl sulfoxide, pyridine, propylene glycol, isopropyl acetate or tetrahydrofuran, and the mass ratio of powder A to the organic solvent is 1-3:15-20.

[0017] Furthermore, the heating and stirring in step 2 is performed at a temperature of 40 to 60° C. for at least 10 hours.

[0018] Furthermore, the fiber film C obtained in step 3 has a thickness of 0.8 to 1.2 mm before drying, and a fiber diameter of 5 to 8 mm.

[0019] Furthermore, the process parameters of the electrospinning in step 3 are:

[0020] Transfer the precursor solution B to a 4-5 mL syringe, keep the distance between the syringe needle nozzle and the drum collector at 15-25 cm, apply a high voltage of 10-15 kV, push the booster at a speed of 1-1.5 mm / min, and electrospin the precursor solution B on a drum collector coated with aluminum foil. Peel the synthesized fibers off the aluminum foil every 6-8 hours to ensure that the fiber thickness is 0.8-1.2 mm.

[0021] Furthermore, the temperature is maintained at 45-50° C. during the electrospinning process to ensure that the precursor solution B has good fluidity.

[0022] Furthermore, in step 4, the plane size of the fiber film C after crushing is 0.2 to 0.5 cm.

[0023] Furthermore, the mixing in step 4 further includes a ball milling process, the ball milling speed is 200 to 500 rpm, and the ball milling time is 2 to 5 hours.

[0024] Furthermore, in step 6, fiber particles are obtained by multiple ball milling.

[0025] Furthermore, the ball milling was performed at a rotation speed of 300 rpm for 3 to 5 minutes each time, and the ball milling was allowed to stand for 20 to 40 minutes to allow the temperature in the ball milling jar to drop to room temperature to prevent excessive temperature accumulation from causing the bound sulfur to separate from the fiber. The ball milling was repeated 30 to 40 times.

[0026] Furthermore, the length of the fiber particles is less than 10 μm.

[0027] An all-solid-state lithium-sulfur battery positive electrode material is obtained by mixing and ball-milling the sulfurized polyacrylonitrile fiber composite material, a sulfide solid electrolyte, and a conductive additive in a mass ratio of (2-4): (2-4): 1.

[0028] Furthermore, the sulfide solid electrolyte is Li 10 Sn2PS 12、Li3PS4、Li7P3S 11 , L 10 GP2S 12 or L6PS5C.

[0029] Furthermore, the conductive additive is conductive carbon black, carbon nanotubes, graphene or vapor-grown carbon fiber.

[0030] An all-solid-state lithium-sulfur battery is assembled based on an all-solid-state lithium-sulfur battery positive electrode material, a sulfide solid electrolyte and a Li-In alloy negative electrode; wherein the sulfide solid electrolyte and the sulfide solid electrolyte used in synthesizing the all-solid-state lithium-sulfur battery positive electrode material are the same material.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. The present invention proposes a method for preparing a vulcanized polyacrylonitrile fiber composite material for an all-solid-state lithium-sulfur battery positive electrode. Through the synthesis process of thiol modification, electrospinning, two-step sintering and multiple ball milling, the combined sulfur content ratio of the positive electrode of the all-solid-state lithium-sulfur battery is increased, which helps to improve the electron and ion transmission at the three-phase contact interface inside the positive electrode of the all-solid-state lithium-sulfur battery, thereby improving the capacity release of the all-solid-state lithium-sulfur battery;

[0033] 2. Specifically, polyacrylonitrile is modified with mercapto groups to capture more sulfur species during the thermal decomposition and cyclization process of the first high-temperature sintering step, thereby increasing the bound sulfur content in the vulcanized polyacrylonitrile fiber composite material, and the crystalline sulfur is removed by the second low-temperature sintering step to improve the electronic conductivity of the positive electrode of the all-solid-state lithium-sulfur battery, thereby ultimately improving the cycle stability of the all-solid-state lithium-sulfur battery;

[0034] 3. Preferably, short and fine fiber particles are constructed by multiple ball milling, and the length of the fiber is reduced to less than 10 μm without destroying the sulfur binding state, so as to further enhance the effective contact area between the fiber particles and the sulfide solid electrolyte and the conductive additive, thereby increasing the three-phase contact interface for efficient transmission of electrons and ions, improving the capacity release of the all-solid-state lithium-sulfur battery, and further improving the various performance indicators of the all-solid-state lithium-sulfur battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0036] Figure 1This is a SEM (scanning electron microscope) image of the vulcanized polyacrylonitrile fiber composite material (denoted as S@SH-PAN) obtained in Example 1;

[0037] Figure 2 This is a SEM magnified image of the vulcanized polyacrylonitrile fiber composite material obtained in Example 1;

[0038] Figure 3 This is a thermogravimetric analysis curve of the vulcanized polyacrylonitrile fiber composite material obtained in Example 1;

[0039] Figure 4 This is a thermogravimetric analysis curve of the vulcanized polyacrylonitrile fiber composite material obtained in Comparative Example 1;

[0040] Figure 5 This is the XRD (X-ray diffraction) diagram of the vulcanized polyacrylonitrile fiber composite material obtained in Example 1;

[0041] Figure 6 This is a CV scan of the all-solid-state lithium-sulfur battery using the sulfurized polyacrylonitrile fiber composite material as the positive electrode obtained in Example 2;

[0042] Figure 7 This is a comparison chart of the long cycle performance of the all-solid-state lithium-sulfur battery with the sulfurized polyacrylonitrile fiber composite material as the positive electrode obtained in Example 2 and Comparative Example 2. DETAILED DESCRIPTION

[0043] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with the examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. All raw materials of the present invention are not particularly limited in their sources, and can be purchased on the market or prepared according to conventional methods well known to those skilled in the art.

[0044] Example 1

[0045] This embodiment provides a method for preparing a vulcanized polyacrylonitrile fiber composite material for an all-solid-state lithium-sulfur battery positive electrode, comprising the following steps:

[0046] Step 1: ball-milling thiocyanate and polyacrylonitrile powders in a mass ratio of 1:1, transferring the mixed powder to a refractory crucible, placing it in a tubular furnace, and sintering it at 150° C. in an argon atmosphere for 3 h to obtain powder A (denoted as SH-PAN).

[0047] Step 2: Powder A was dissolved in N,N-dimethylformamide at a mass ratio of 2:15, and the mixture was heated at 60° C. and stirred vigorously for 12 h to form a uniform precursor solution B.

[0048] Step 3: Transfer the precursor solution B to a 5 mL plastic syringe, keep the distance between the syringe needle nozzle and the drum collector at 15 cm, apply a high voltage of 15 kV to the prepared precursor solution B, and the booster push speed is 1 mm / min. The precursor solution B is electrospun on a drum collector coated with aluminum foil, and continuously heated during the electrospinning process, and the temperature is maintained at 45°C; the synthesized fibers are peeled off the aluminum foil every 6 hours, and the collected fibers are dried in a 60°C forced air oven to remove the remaining N,N-dimethylformamide to obtain a fiber film C.

[0049] Step 4: Place the fiber film C in a small fiber crusher for crushing. The crushed fiber pieces have a plane size of about 0.5 cm. Then mix them with sulfur powder in a mass ratio of 4:1, transfer them to a planetary ball mill for ball milling, control the speed at 400 rpm, and ball mill for 3 hours to obtain a mixture D.

[0050] Step 5: Place the mixture D into a refractory crucible, place it in a tubular furnace, raise the temperature to 350°C in an argon environment, and keep it warm for 6 hours to complete the vulcanization process; then reduce the temperature to 150°C and keep it warm for 3 hours to remove the crystalline sulfur; wait for the tubular furnace to cool naturally to room temperature, and take out the fiber sintered material E.

[0051] Step 6: Place the fiber sintered material E into a swing ball mill, mill it at a speed of 300 rpm for 3 minutes each time, let it stand for 20 minutes to allow the temperature in the ball mill to drop to room temperature, and mill it again. Repeat this cycle 30 times to obtain the vulcanized polyacrylonitrile fiber composite material (denoted as S@SH-PAN).

[0052] Comparative Example 1

[0053] This comparative example provides a method for preparing a vulcanized polyacrylonitrile fiber composite material for an all-solid-state lithium-sulfur battery positive electrode. The steps are different from those in Example 1, except that step 5 is only kept at 350°C for 6 hours, and does not include cooling to 150°C for 3 hours to remove crystalline sulfur; the remaining steps remain unchanged. Finally, a vulcanized polyacrylonitrile fiber composite material (denoted as SPAN) is obtained.

[0054] The vulcanized polyacrylonitrile fiber composite material synthesized in Example 1 was subjected to scanning electron microscopy observation, thermogravimetric analysis, organic element analysis test and X-ray diffraction analysis.

[0055] Figure 1 and Figure 2This is the SEM image of the vulcanized polyacrylonitrile fiber composite material obtained in Example 1. It can be seen that the fiber particles of the vulcanized polyacrylonitrile fiber composite material are short and thin, with a length of less than 10 μm, so that the all-solid-state lithium-sulfur battery positive electrode material based on the vulcanized polyacrylonitrile fiber composite material has a larger surface area, and has more contact area with the sulfide solid electrolyte and the conductive additive, which is beneficial to the transmission of ions and electrons inside the positive electrode of the all-solid-state lithium-sulfur battery.

[0056] Figure 3 This is the thermogravimetric analysis curve of the vulcanized polyacrylonitrile fiber composite material obtained in Example 1. It can be seen that the mass loss in the temperature range of 112 to 300°C (i.e., stage II) is only about 5%, and the mass loss in this stage mainly comes from the elemental sulfur species. It can be seen that elemental sulfur only accounts for 5% of the total mass of the vulcanized polyacrylonitrile fiber composite material.

[0057] Figure 4 This is a thermogravimetric analysis curve of the vulcanized polyacrylonitrile fiber composite material obtained in Comparative Example 1. It can be seen that the mass loss in the temperature range of 112 to 300°C (i.e., stage II) is as high as 30%. It can be seen that elemental sulfur accounts for about 30% of the total mass of the vulcanized polyacrylonitrile fiber composite material, indicating that compared with Comparative Example 1, the electronic conductivity of the vulcanized polyacrylonitrile fiber composite material obtained in Example 1 is greatly improved.

[0058] Table 1 shows the organic element analysis test results of the vulcanized polyacrylonitrile fiber composite material obtained in Example 1. Two samples of vulcanized polyacrylonitrile fiber composite materials prepared in the same batch were used for the test, wherein the total content of sulfur species was about 36%, and the elemental sulfur obtained by thermogravimetric analysis accounted for about 5%. It can be seen that the bound sulfur content in the vulcanized polyacrylonitrile fiber composite material is about 30%. By removing the crystalline sulfur element in step 5, the electronic conductivity of the all-solid-state lithium-sulfur battery positive electrode material based on the vulcanized polyacrylonitrile fiber composite material can be improved.

[0059] Table 1

[0060] Sample No. N(%) C(%) H(%) S(%) O(%) 1 18.194 37.212 1.529 36.011 / 2 18.722 37.175 1.57 35.884 /

[0061] Figure 5 This is the XRD diagram of the vulcanized polyacrylonitrile fiber composite material obtained in Example 1, wherein the characteristic peaks of the sulfur (100), (102) and (110) crystal planes of the vulcanized polyacrylonitrile fiber composite material disappear, indicating that the synthesized vulcanized polyacrylonitrile fiber composite material is mainly composed of amorphous phase bound sulfur.

[0062] Example 2

[0063] In this embodiment, the sulfurized polyacrylonitrile fiber composite material obtained in Example 1 is used to synthesize the positive electrode material of the all-solid-state lithium-sulfur battery, and then the all-solid-state lithium-sulfur battery is assembled.

[0064] Specifically, the vulcanized polyacrylonitrile fiber composite material obtained in Example 1 was mixed with L 10 GP2S 12 , carbon nanotubes in a mass ratio of 4:2:1, ground in a glove box for 40 minutes, transferred to a planetary ball mill, and sealed with sealing glue; the ball mill was taken out of the glove box, placed in a planetary ball mill for ball milling and mixing, the speed was set to 200 rpm, the ball milling time was 10 hours, and after the ball milling was completed, the ball mill was transferred to the glove box and the ball milled material was taken out, i.e., the positive electrode material of the all-solid-state lithium-sulfur battery.

[0065] The obtained all-solid-state lithium-sulfur battery positive electrode material is used as the positive electrode and the electrolyte L 10 GP2S 12 , Li-In alloy negative electrode is assembled into an all-solid-state lithium-sulfur battery.

[0066] Comparative Example 2

[0067] In this comparative example, an all-solid-state lithium-sulfur battery positive electrode material is synthesized from the sulfurized polyacrylonitrile fiber composite material obtained in comparative example 1, and then an all-solid-state lithium-sulfur battery is assembled. The process is compared with that in example 2, except that the sulfurized polyacrylonitrile fiber composite material obtained in example 1 is replaced by the sulfurized polyacrylonitrile fiber composite material obtained in comparative example 1; the rest of the process is the same.

[0068] The all-solid-state lithium-sulfur battery obtained in Example 2 was subjected to constant current charge and discharge test on a blue electric test system, with the voltage range set to 0.5-2.5V. The test results are as follows Figure 6 The CV scan diagram shown in the figure shows that the all-solid-state lithium-sulfur battery with sulfurized polyacrylonitrile fiber composite material (S@SH-PAN) as the positive electrode active material does not introduce unnecessary redox reactions, the reversibility of the electrode reaction is good, and the battery has a high current response, a small polarization voltage, and good reaction kinetics.

[0069] The all-solid-state lithium-sulfur batteries obtained in Example 2 and Comparative Example 2 were subjected to cyclic voltammetry test on an electrochemical workstation with the scan rate set to 0.1 mV / s. Figure 7 As shown in the long cycle performance comparison chart, it can be seen from the figure that compared with the all-solid-state lithium-sulfur battery with sulfurized polyacrylonitrile fiber composite material (SPAN) as the positive electrode material in Comparative Example 2, the all-solid-state lithium-sulfur battery with sulfurized polyacrylonitrile fiber composite material (S@SH-PAN) as the positive electrode material in Example 2 releases more capacity, and the initial capacity is as high as 928 mAh / g, which is much higher than 368 mAh / g of Comparative Example 2, indicating that the sulfurized polyacrylonitrile fiber composite material obtained in Example 1 helps to improve the electron and ion transport at the three-phase contact interface inside the positive electrode of the all-solid-state lithium-sulfur battery, thereby improving the capacity release.

[0070] Example 3

[0071] This embodiment provides a method for preparing a vulcanized polyacrylonitrile fiber composite material for an all-solid-state lithium-sulfur battery positive electrode. The steps are different from those in Example 1, except that the mass ratio of thiocyanuric acid and polyacrylonitrile powder in step 1 is adjusted from 1:1 to 1:5, and the sintering temperature is adjusted to 250°C; the remaining steps remain unchanged.

[0072] Example 4

[0073] This embodiment provides a method for preparing a vulcanized polyacrylonitrile fiber composite material for an all-solid-state lithium-sulfur battery positive electrode. The steps are different from those in Example 1, except that the mass ratio of 2:15 in step 2 is adjusted to 1:20; the remaining steps remain unchanged.

[0074] Example 5

[0075] This embodiment provides a method for preparing a vulcanized polyacrylonitrile fiber composite material for an all-solid-state lithium-sulfur battery positive electrode. The steps are compared with those in Example 1, and the only difference is that: in step 3, "peeling the synthetic fiber off the aluminum foil every 6 hours" is adjusted to "peeling the synthetic fiber off the aluminum foil every 8 hours" to increase the thickness of the fiber film C; the other steps remain unchanged.

[0076] Example 6

[0077] This embodiment provides a method for preparing a vulcanized polyacrylonitrile fiber composite material for an all-solid-state lithium-sulfur battery positive electrode. The steps are compared with those in Example 1, except that the sintering temperature for removing crystalline sulfur in step 5 is adjusted to 200° C. and the holding time is adjusted to 2 h; the remaining steps remain unchanged.

[0078] The present invention uses specific examples to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enables any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements that are not different from the text of the claims, or if they include equivalent structural elements that are not substantially different from the text of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A method for preparing a vulcanized polyacrylonitrile fiber composite material for an all-solid-state lithium-sulfur battery positive electrode, characterized in that: The following steps are involved: Step 1: mixing a small molecule organic substance containing a thiol functional group with polyacrylonitrile, and sintering the mixture in a rare gas atmosphere or nitrogen to obtain powder A; Step 2, dissolving powder A in an organic solvent, heating and stirring to form a precursor solution B; Step 3, spinning the precursor solution B into fibers through an electrospinning process, and drying to obtain a fiber film C; Step 4, crushing the fiber film C, and mixing it with sulfur powder in a mass ratio of (3-5):1 to obtain a mixture D; Step 5, placing the mixture D in a rare gas atmosphere or nitrogen, heating it to 250-450° C., and keeping it warm for 5-8 hours; then cooling it to 150-200° C., keeping it warm for 2-4 hours, and cooling it to room temperature to obtain a fiber sintered material E; Step 6: ball-mill the fiber sintered material E into fiber particles to obtain a sulfurized polyacrylonitrile fiber composite material for the positive electrode of an all-solid-state lithium-sulfur battery.

2. The method for preparing the vulcanized polyacrylonitrile fiber composite material for the positive electrode of an all-solid-state lithium-sulfur battery according to claim 1, characterized in that: The small molecule organic compound containing a thiol functional group in step 1 is tert-butyl mercaptan, trithiocyanate, cysteine, cysteamine, sodium methyl mercaptan, thioglycolic acid, naphthalene dithiol or mercaptoethylamine hydrochloride, and the mass ratio of the small molecule organic compound containing a thiol functional group to polyacrylonitrile is 1:1 to 5.

3. The method for preparing the vulcanized polyacrylonitrile fiber composite material for the positive electrode of an all-solid-state lithium-sulfur battery according to claim 1, characterized in that: In step 1, the sintering temperature is 150-250° C. and the sintering time is 3-5 hours.

4. The method for preparing the vulcanized polyacrylonitrile fiber composite material for the positive electrode of an all-solid-state lithium-sulfur battery according to claim 1, characterized in that: The organic solvent in step 2 is N,N-dimethylformamide, dimethyl sulfoxide, pyridine, propylene glycol, isopropyl acetate or tetrahydrofuran, and the mass ratio of powder A to the organic solvent is 1-3:15-20.

5. The method for preparing the vulcanized polyacrylonitrile fiber composite material for the positive electrode of an all-solid-state lithium-sulfur battery according to claim 1, characterized in that: The heating and stirring in step 2 is performed at a temperature of 40 to 60° C. for at least 10 hours.

6. The method for preparing the vulcanized polyacrylonitrile fiber composite material for the positive electrode of an all-solid-state lithium-sulfur battery according to claim 1, characterized in that: The fiber film C obtained in step 3 has a thickness of 0.8 to 1.2 mm before drying, and a fiber diameter of 5 to 8 mm.

7. The method for preparing the vulcanized polyacrylonitrile fiber composite material for the positive electrode of an all-solid-state lithium-sulfur battery according to claim 1, characterized in that: Step 6: The fiber particles are obtained by ball milling for multiple times, specifically at a rotation speed of 300 rpm, each ball milling for 3 to 5 minutes, standing for 20 to 40 minutes to allow the temperature in the ball mill to drop to room temperature, and repeating the ball milling for 30 to 40 times.

8. The method for preparing the vulcanized polyacrylonitrile fiber composite material for the positive electrode of an all-solid-state lithium-sulfur battery according to claim 7, characterized in that: The length of the fiber particles is less than 10 μm.

9. An all-solid-state lithium-sulfur battery positive electrode material, characterized in that: The method is obtained by mixing and ball-milling the sulfurized polyacrylonitrile fiber composite material for the positive electrode of an all-solid-state lithium-sulfur battery according to any one of claims 1 to 8 with a sulfide solid electrolyte and a conductive additive in a mass ratio of (2 to 4): (2 to 4):

1.

10. An all-solid-state lithium-sulfur battery, characterized in that: The all-solid-state lithium-sulfur battery positive electrode material, the sulfide solid electrolyte and the Li-In alloy negative electrode are assembled based on claim 9; wherein the sulfide solid electrolyte and the sulfide solid electrolyte used in synthesizing the all-solid-state lithium-sulfur battery positive electrode material are the same material.

Citation Information

Patent Citations

  • Organic sulfur positive electrode material, preparation method thereof and application of organic sulfur positive electrode material in battery

    CN116779852A

  • Sulfur-polyacrylonitrile composite, preparation and use thereof

    WO2016019544A1